The role of the partner in the support of a pregnant woman's healthy diet: an explorative qualitative study - Renske M. van Lonkhuijzen; Hanna Rustenhoven; Jeanne H. M. de Vries; Annemarie Wagemakers (BMC, 2023)
Abstract Background Active partner involvement during pregnancy is an effective strategy to enhance both maternal and newborn health outcomes. The presence of a supportive partner equips women with a heightened sense of empowerment to deal with the challenges of pregnancy, including maintaining a healthy diet during pregnancy, which is important for the health of both the mother and child. However, little information exists regarding the partner's role in encouraging a pregnant woman's healthy dietary choices. This study aimed to explore the perspectives of pregnant women and their partners concerning the partner's role in promoting a healthy dietary intake during pregnancy. Methods Sixteen semi-structured couple interviews were conducted in the Netherlands, involving expecting couples. Based on Berkman's social networks and support theory, we categorized various forms of support as emotional, instrumental, appraisal, and informational. The interviews were accurately recorded, transcribed verbatim, and analysed using an inductive approach. Results In general, pregnant women reported being positive regarding the support they received from their partners. Partners primarily offered instrumental support to pregnant women, such as cooking, grocery shopping, and helping them avoid unsafe foods. Partners provided informational support, mainly about foods considered unsafe during pregnancy. Emotional support was relatively less common. The primary motives for giving support were pregnancy-related symptoms, the importance of the health of the mother and baby, and solidarity with the pregnant woman. Support from the partner was more willingly accepted by pregnant women if the support was perceived as being helpful, showing involvement, and positive. Conversely, partner support was not accepted if it was perceived as judgmental or unwanted. Conclusions The majority of pregnant women were satisfied with the support received from their partners, although there are opportunities for a partner to provide more support to improve the dietary intake of pregnant women. To optimise this support, partners are advised to tailor their support to the needs and expectations of pregnant women. Personalizing dietary support can be achieved by couples communicating their dietary wishes and expectations regarding support.